Petrography of the Loe Shilman Carbonatite complex, Khyber Agency - Jan, M. Qasim; Kamal, Muhammad; Qureshi, Aziz A. (Journal of Himalayan Earth Sciences, 1981)
The Shilman complex comprises sill-form bodies emplaced along a fault zone in Palaeozoic to Precambrian metasedimentary rocks. The largest outcrop is 2.5 Km long with u width of 170 m in the central part. The rock-types of the complex include altered (metn) gabbros/dolerite, followed by amphibole-apatite-, biotite/phlogopite-, and dolomitic carbonatites, syenites and lamprophyric rocks, and Fe-rich hydrothermal veins. The syenitic rocks have locally been intruded and brecciated by light-coloured sovitic veins. It is suggested that the basic rocks might be related to the rest of the complex. The country rocks (slates, phyllites, mica schists, recrystallized limestone and quartzite) have been regionally metamorphosed up to the biotite zone of Barrovian. They display, locally, considerable fenitization with development of alkali pyroboles, phlogopite and alkali feldspars. The complex is a westward extension of the over 200 Km urcuate belt of dkaliuze complexes found around the northern half of the Peshawar Plain and intruded during Early Tertiary along faults resulting due to the collision of the Indo-Pak plate with Eurasia.